A Review: Evaluation of Black Soldier Fly (Hermetia illucens) Larvae Meal as a Dietary Protein Source in Poultry Diets - Purnamasari, Listya; Lopez, Zandrelle P; dela Cruz, Joseph F. (Universitas Brawijaya, 2022)
The increasing global population poses a problem in achieving food security. Poultry is one of the major animal protein sources for humans and the main difficulty of the poultry industry is seeking a suitable protein alternative to be integrated into poultry feed. Black soldier fly larvae (BSF) (Hermetia illucens) are one of the edible insects that are a great solution to this problem since they have various advantages, which include bioconversion of different organic wastes and the absence of competition for human resources. Several studies have already examined the effects of the addition of BSF larvae in the poultry diet, and most suggested that it is a promising alternative protein source that can replace soy or fish meal. The BSF larvae can also be used in different species of poultry, such as ducks, turkeys, and quails. However, there are several barriers to using BSF larvae as a feed ingredient in poultry feed, such as safety, price, and consumer acceptance. Despite these obstacles, BSF larvae production is still a promising industry due to the numerous benefits it brings.